KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI PEMBELAJARAN PENEMUAN TERBIMBING - Irsal, Irni Latifa (Institut Agama Islam Negeri Curup, 2020)
The gap between facts and the importance of problem solving skill to be developed, into cornerstone of this research. Research of improving students? problem solving skill through guided discovery learning is the aim of this research. Qualitative descriptive be the method in this research. Pre-test and post-test was completed by 38 students. Pre-test and post-test result were analyzed descriptively. To get in-depth data about students? problem solving ability, interviews were conducted with 20 students. Results of interviews, observations, and research journals were analyzed qualitatively. There is a difference in the improvement of problem solving skill, seen from the increase on total value and the increase on each indicator of problem solving skill. In total value, the increase have is in the low category. Also the increase of 1st indicator and 3rd indicator is in thw low category. But, indicator 2nd and 4th is in the medium category.